Hubungan Antara Kecanduan Game Online Dengan Perilaku Agresif Pada Remaja Di Mabar Hilir Kota Medan - Sri Aulia; Andy Chandra; Khairuddin Khairuddin (Universitas Medan Area, 2022)
This study used quantitative correlational aimed to find out the relationship between online gaming addiction and aggressive behavior in adolescents in the lower reaches of medan cities. Aggression is the behavior of hurting a person, both physically and psychologically. One of the factors of aggressive behavior is addiction to online games. Online gaming addiction is the inability to control the behavior of playing online games that causes social problems and emotional problems for the perpetrator. The sample in this study was 70 people using quota sampling techniques based on criteria: adolescents who played fighting online games, played for at least one year, played online games at least 3 hours per day or 20-25 hours a week. Data capture uses a scale of online gaming addiction and aggressive behavior tested using product moments. Based on the results of the analysis it is known that there is a positive association of online gaming addiction with aggressive behavior, where rxy = 0.600 with a significant p = 0.000 0.05. This means that the hypothesis is that there is a positive relationship of online gaming addiction with aggressive behavior. Assuming the higher the addiction to online gaming then the aggressive behavior is higher, and vice versa. Hypothesis accepted. The determinant coefficient (r2) of the relationship between variable X and variable Y of r2 = 0.360, this indicates that online gaming addiction contributes to aggressive behavior by 36%. There are still 64% of other factors that influence aggressive behavior.